Family environment, children's acculturation and mothers' dietary intake and behaviors among Latinas: An autoregressive cross-lagged study. (May 2019) - Soto, Sandra H.; Arredondo, Elva M.; Shakya, Holly B.; Roesch, Scott; Marcus, Bess; Parada, Humberto; Ayala, Guadalupe X.
Abstract: Background: Many Latinos in the U.S. do not meet dietary recommendations for healthy eating. Family systems theory posits that the family environment affects family members' dietary behaviors. Moreover, research suggests that children's acculturation is associated with Latina mothers' dietary intake and behaviors. Purpose: This longitudinal study examined the effect of the family environment on Latina mothers' dietary intake and behaviors. Further, we examined whether these effects differed between mothers of assimilated versus bicultural children. Methods: Secondary data were collected at three time points (baseline, and four and 10 months' post-baseline) from 162 culturally traditional and bicultural Latina mothers residing in Imperial County, California, U.S. Participants were enrolled in the delayed treatment group of a randomized controlled trial. Mothers' daily fruit, vegetable, and sugary beverages intake, percent of calories from fat, weekly away-from-home eating, and percent of weekly grocery dollars spent on fruits and vegetables were examined. The family environment was measured by family expressiveness and family interactions around food. Separate autoregressive cross-lagged models examined the effects of the family environment on dietary outcomes, adjusting for sociodemographic variables. Interactions between the family environment and children's acculturation were also tested. Results: Less positive family interactions around food at baseline predicted more frequent away-from-home eating four months later among mothers of assimilated children. More family expressiveness at four months predicted more grocery dollars spent on fruits and vegetables at ten months among mothers of bicultural children. Conclusions: Findings suggest the importance of a positive family environment on socially-bound dietary behaviors (e.g., away-from-home eating) exhibited by the mother. Family interventions aimed at improving dietary intake and associated behaviors should promote a positive family environment around food and consider the moderating role of children's acculturation. Highlights: We modeled longitudinal links between family environment and Latina mothers' diets. We further tested interactions between child acculturation and family environment. A positive family environment was important to socially-bound dietary behaviors. These associations were found among mothers of bicultural vs. assimilated children.